The language construction of Muslims as the others in French contemporary discourses - Wening Udasmoro (Indonesian Journal of Islam and Muslim Societies, 2017)
This article intends to explain the Muslims position in French contemporary discourses. France is a secular country, based on the principle of laïcité (separation between religion and State). France is also the country with the largest Muslim population in Europe. Muslims’ positions, as with others’, cannot be separated from the varied discourses in everyday life disseminated through different vehicles such as the media, literature, and conversations in society. Talking about the discourse of otherness is important to strengthenthe argument that the social relation patterns in France, where there hasbeen tension between Muslims and the French people in recent years, are not simply political or social questions. They are also language constructions. The Bourdieusian perspective explains how social construction is closely connected to language construction. Fear of Muslims, on the one hand, is related to political and social tensions, but on the other hand it is also related to language consumption and the historically constructed othering process. Based on the above situation, this article asks: first, in contemporary French discourses, what stereotypes regarding Islam and Muslims are represented in everyday language? Second, in which context do these stereotypes appear? Third, how are the language effects of the stereotypes of otherness, which serve as mental models for positioning the Other, operatedas social practices? Artikel ini bermaksud untuk menjelaskan posisi Muslim dalam diskursus Prancis kontemporer. Prancis adalah negara sekular, berbasis pada prinsip laïcité (pemisahan antara agama dan negara). Prancis juga merupakan negara dengan populasi Muslim terbesar di Eropa. Posisi Muslim “sebagai liyan”, tidak dapat dipisahkan dari berbagai diskursus sehari-hari yang terdeseminasi lewat berbagai kendaraan, seperti media, sastra, dan percakapan sehari-hari dalam masyarakat. Berbicara mengenai diskursus liyan menjadi penting untuk memperkuat argumen bahwa pola-pola hubungan sosial di Prancis, dimana ada ketegangan antara Muslim dan orang Prancis non Muslim akhir-akhir ini, bukanlah sekedar persoalan politik dan sosial. Ada pula persoalan konstruksibahasa. Perspektif Bourdieusian menjelaskan bagaimana konstruksi sosial berhubungan erat dengan konstruksi bahasa. Ketakutan pada Muslim, di satu sisi, berhubungan erat dengan ketegangan politik dan sosial, namun di sisi lain, hal ini terkait pula dengan konsumsi dan konstruksi historis dalam proses peliyanan. Berdasarkan situasi di atas, beberapa pertanyaan diajukan: pertama, dalam diskursus Prancis kontemporer, stereotip apa yang terdapat dalam diskursus sehari-hari terhadap Islam dan Muslim? Kedua, dalam konteks apa diskursus ini muncul? Ketiga, bagaimana efek bahasa terkait dengan stereotipterhadap liyan, yang merupakan model mental dalam memosisikan liyan dalam praktik sosial tersebut?